Penegakan Hukum terhadap Pelaku Tindak Pidana Penyalahgunaan Gas Bumi Bersubsidi - Nirma Sri Asyfa; Suwari Akhmaddhian (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
Natural gas, as a strategic resource, undergoes various stages in exploration, exploitation, and processing to become downstream products such as Liquefied Petroleum Gas (LPG), a product of natural gas management aimed at supporting government energy policies to assist vulnerable communities. However, misuse of subsidized natural gas remains common. Based on this, this article examines the case of Decision No. 151/Pid.B/LH/2022/PN Kdr. The purpose of this article is to determine the effectiveness of regulations in managing natural gas distribution and to understand how the legal system can support more effective enforcement. The research method used is normative juridical. The analysis concludes that the application of natural gas regulations to address the misuse of subsidized LPG distribution can be seen in how these regulations serve as the legal basis for protecting energy subsidies from practices detrimental to the public and the state. The application of legal system theory to this case demonstrates that the misuse of subsidized gas is not only caused by weaknesses in the legal structure or legal substance but also influenced by the existing legal culture.